Biochanin A as a modulator of the inflammatory response: An updated overview and therapeutic potential - Franciel Batista Felix; Juliana Priscila Vago; Vinícius Amorim Beltrami; Jessica Maria Dantas Araújo; Renata Grespan; Mauro Martins Teixeira; Vanessa Pinho (Elsevier, 2022)
Uncontrolled inflammation and failure to resolve the inflammatory response are crucial factors involved in the progress of inflammatory diseases. Current therapeutic strategies aimed at controlling excessive inflammation are effective in some cases, though they may be accompanied by severe side effects, such as immunosuppression. Phytochemicals as a therapeutic alternative can have a fundamental impact on the different stages of inflammation and its resolution. Biochanin A (BCA) is an isoflavone known for its wide range of pharmacological properties, especially its marked anti-inflammatory effects. Recent studies have provided evidence of BCA's abilities to activate events essential for resolving inflammation. In this review, we summarize the most recent findings from pre-clinical studies of the pharmacological effects of BCA on the complex signaling network associated with the onset and resolution of inflammation and BCA's potential protective functionality in several models of inflammatory diseases, such as arthritis, pulmonary disease, neuroinflammation, and metabolic disease.